The effect of RADEC model on reading comprehension ability - Amaliyah, Risma Nur; Wati, Tri Linggo (CAHAYA PENDIDIKAN, 2024)
Reading comprehension is an activity carried out by an individual to be able to get the core of the message expressed by the author in understanding the meaning through a text or word media. Reading comprehension skills are an important component to help learners master various concepts so that they can find and understand a lot of information. By reading and understanding it, learners are expected to understand the core of the reading they read and can get something useful. The RADEC (Read-Answer-Discuss-Explain and Create) learning model is a model that uses stages in learning according to the name of the model, namely reading, answering, discussing, explaining and creating. This study aims to find a solution to reading comprehension problems using the RADEC model. This research uses a quantitative method of experimental type using a pre-experimental design using the One-Group Pretest Post-test Design model with a sample size of 30 students. Data analysis techniques using normality test, descriptive analysis, Wilcoxon test, and making conclusions. The normality test results are not normally distributed because the Sig value